2021
DOI: 10.3389/fpsyt.2021.723158
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effect of Serum Lipids and Body Mass Index on Psychotic Symptoms, a Cross-Sectional Study of First-Episode Psychosis Patients

Abstract: Background: Schizophrenia is a disorder with considerable heterogeneity in course and outcomes, which is in part related to the patients' sex. Studies report a link between serum lipids, body mass index (BMI), and therapeutic response. However, the role of sex in these relationships is poorly understood. In a cross-sectional sample of first-episode psychosis (FEP) patients, we investigated if the relationship between serum lipid levels (total cholesterol, HDL-C, LDL-C, and triglycerides), BMI, and symptoms dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
2
2
0
Order By: Relevance
“…In short, such findings may help explain our results, which found that the effect of TG on ECN‐related inter‐network FC was sex‐dependent. Our results, together with those of previous studies (Gjerde et al., 2021 ; Seyfried et al., 2018 ; Xu et al., 2021 ; Yin et al., 2018 ), suggest that alterations in inter‐network FC may be a potential network mechanism of lipid‐involved neuropsychiatric disorders that exhibit sex dimorphism.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In short, such findings may help explain our results, which found that the effect of TG on ECN‐related inter‐network FC was sex‐dependent. Our results, together with those of previous studies (Gjerde et al., 2021 ; Seyfried et al., 2018 ; Xu et al., 2021 ; Yin et al., 2018 ), suggest that alterations in inter‐network FC may be a potential network mechanism of lipid‐involved neuropsychiatric disorders that exhibit sex dimorphism.…”
Section: Discussionsupporting
confidence: 85%
“…Our results, together with those of previous studies (Gjerde et al, 2021;Seyfried et al, 2018;Xu et al, 2021;Yin et al, 2018), suggest that alterations in inter-network FC may be a potential network mechanism of lipid-involved neuropsychiatric disorders that exhibit sex dimorphism.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In recent years, there have been numerous studies examining the relationship between MDD patients and biochemical markers, aiming to explore measurable indicators for MDD patients [16][17][18]. Additionally, there is substantial evidence indicating a connection between hormone levels [19][20][21]and metabolic markers [22,23] to PS in MDD patients. To illustrate, Contreras et al discovered that approximately 80% of depression samples exhibited at least one hormonal axis disturbance, with 40.0% and 5.0% experiencing two and three hormone axis disturbances, respectively [19].…”
Section: Introductionmentioning
confidence: 99%